Insentif Pajak, Pemahaman Perpajakan, Lingkungan Sosial, dan Kepatuhan WPOP UMKM Pada Pandemi Covid-19 - Putri, Komang Devinta Riani; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 34 No 2 (2024), 2024)
Taxpayer compliance is the behavior of a taxpayer who complies with his tax obligations in accordance with the rules. The aim of this research is to examine the influence of tax incentives, understanding of taxation, and the social environment on MSME individual taxpayer compliance during the Covid-19 Pandemic at the East Denpasar Pratama Tax Service Office. The population in this research is all MSME individual taxpayers registered at KPP Pratama East Denpasar amounting to 4,239 taxpayers. The sample used was 98 respondents and was determined using the Slovin formula. The method for determining the sample in this research is non-probability sampling, especially purposive sampling. The data analysis technique used is descriptive statistical analysis and partial least squares. Based on the research results, it shows that tax incentives, understanding of taxation and the social environment have a positive and significant influence on MSME individual taxpayer compliance during the Covid-19 pandemic. Keywords:Tax Incentives, Understanding, Environment, Compliance.